Strain effect on the electronic and optical properties of 2D Tetrahexcarbon: a DFT-based study - Hoat, D. M.; Amirian, Shirin; Alborznia, Hamidreza; Laref, Amel; Reshak, A. H.; Naseri, Mosayeb (Indian journal of physics, 2021)
A new two-dimensional (2D) carbon allotrope, namely Tetrahexcarbon (TH-carbon) semiconductor monolayer with a direct band gap resides in the visible region of the electromagnetic spectra, has been recently proposed theoretically. Herein, the influences of biaxial strains on the electrical and optical aspects of 2D TH-carbon are computationally investigated. To this end, first-principles calculations based on the properties of the density functional theory were employed. According to our simulations, the electronic and optical properties of 2D TH-carbon are effectively sensitive to the external strain effects. This obtained strain sensitivity suggests that this 2D material could be a promising material for usage in new electronic technologies. Graphic abstract